If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5x + -10) = 2(x + -2) Reorder the terms: 5(-10 + 5x) = 2(x + -2) (-10 * 5 + 5x * 5) = 2(x + -2) (-50 + 25x) = 2(x + -2) Reorder the terms: -50 + 25x = 2(-2 + x) -50 + 25x = (-2 * 2 + x * 2) -50 + 25x = (-4 + 2x) Solving -50 + 25x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -50 + 25x + -2x = -4 + 2x + -2x Combine like terms: 25x + -2x = 23x -50 + 23x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -50 + 23x = -4 + 0 -50 + 23x = -4 Add '50' to each side of the equation. -50 + 50 + 23x = -4 + 50 Combine like terms: -50 + 50 = 0 0 + 23x = -4 + 50 23x = -4 + 50 Combine like terms: -4 + 50 = 46 23x = 46 Divide each side by '23'. x = 2 Simplifying x = 2
| 81v^2-16=0 | | 2x^2+9x+2=0 | | -3=-3x+1+2x | | 9y=5x | | X-1=-3 | | 10x-7x+x=-3 | | 3+7x=59 | | w^2+7w+12=0 | | 6m+3m-5=49 | | 2x+5=x-1 | | t(5t+3)=0 | | 10p^2(p+1)=5(p+1)-23p(p+1) | | 8n-12=4 | | y+3=15 | | (x-4)(5x+7)= | | 6-4x=7x-9x+10 | | -20r=-420 | | m-7=12 | | 8x(x-3)=(2x+7)(x-3) | | 90=x+18 | | 8xc-8=48 | | y=-3.5+-0.5x | | 3y(y+4)=15 | | 2v^2=8v | | (x-9)(x^2+9x+81)= | | 5b^2+32b+35=0 | | x+5(x-2)=2(x-2)-18 | | 7=3+x | | 76-4=10 | | 4x-3-3(-5x-1)=-57 | | x-6=45 | | 5(x-1)+3x=11 |